2014
DOI: 10.1007/s00384-014-2069-6
|View full text |Cite
|
Sign up to set email alerts
|

Hartmann’s procedure in rectal cancer: a population-based study of postoperative complications

Abstract: Few rectal cancer patients, operated with Hartmann's procedure, developed pelvic complications despite a higher age, more co-morbidities, metastases in different localities and functional inferiority when compared with the patients operated with anterior resection or abdominoperineal excision. Hartmann's procedure is a valid alternative procedure in the old and frail rectal cancer patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 9 publications
3
40
0
1
Order By: Relevance
“…However, another current study described an incidence of 3% for pelvic abscesses and an overall pelvic complication rate of 11% associated with HP in rectal cancer patients [11]. This was significantly lower than with APE (32%) although the HP population was older, had more comorbidities, more stage IV disease, and functional inferiority.…”
Section: Discussionmentioning
confidence: 97%
“…However, another current study described an incidence of 3% for pelvic abscesses and an overall pelvic complication rate of 11% associated with HP in rectal cancer patients [11]. This was significantly lower than with APE (32%) although the HP population was older, had more comorbidities, more stage IV disease, and functional inferiority.…”
Section: Discussionmentioning
confidence: 97%
“…Although the complication rate after HP is reported to be lower, the risk of pelvic abscesses as a consequence of either an infected haematoma or a blowout of the rectal remnant should not be ignored. The incidence varies from 3 to 30% [18, 3537]. HP has also been advocated in the palliative setting as an alternative for patients with disseminated disease, where the benefits of symptomatic relief must exceed the risk of morbidity or mortality [17, 19, 31, 36, 38].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, patients with colon cancer were included and the registry named SCRCR [18]. The SCRCR is a national population-based registry that prospectively collects data for all patients with colorectal cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the protective stoma is controversial, but it is accepted that stoma can reduce the incidence of AL [4,18,19,23]. However, the new method of PNA which we describe in our study showed that it is a good alternative for multi-stage complex restorative operation.…”
Section: Figurementioning
confidence: 59%
“…The second stage -reconstructive surgery is one of the most complicated operation in abdominal surgery with a high percentage of postoperative complications. The frequency restoration of physiologic passage through the colon can be performed only in 30-40% of patients [18,19].…”
Section: Introductionmentioning
confidence: 99%